Natural State Notables : Twenty-One Famous People from Arkansas - Teske, Steven, 1962- (Book collections on Project MUSE., 2013)
Steven Teske is an archivist at the Butler Center for Arkansas Studies, part of the Central Arkansas Library System, and he teaches history at the Arkansas State University. He is the author of Unvarnished Arkansas and the coauthor of Homefront Arkansas.